Dataset_Profiles_Smartphone_Emotional_intelligence_FOMO. - García-Canalejas, María; Chamizo-Nieto, María Teresa; Rey-Peña, Lourdes (Universidad de Málaga, 2025)
Background: Adolescents are the most vulnerable population for problematic smartphone use (PSU). The scientific literature provides evidence that factors such as fear of missing out (FoMO) and emotional intelligence (EI) can be related to problematic internet behaviours, but few studies have been conducted on PSU in adolescents. This study aimed to examine how FoMO and EI might explain PSU in adolescents. Methods: The sample consisted of 537 students (12–17 years old) who completed scales assessing problematic smartphone use, fear of missing out, and emotional intelligence. Results: The results showed in both cases moderate, significant and positive correlations between PSU and FoMO, while significant and negative correlations between PSU and EI were observed. In addition, high FoMO and deficits in EI were found to explain part of the variance in PSU. Conclusions: The results are discussed based on the Theory of compensatory internet use. The need to address EI and FoMO in educational contexts is also justified.
Keywords: Teléfonos móviles y jóvenes; Inteligencia emocional; Adolescentes - Psicología; problematic smartphone use; fear of missing out; emotional intelligence; adolescents